2016
DOI: 10.1007/s11357-016-9897-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic training on markers of autophagy in the elderly

Abstract: Autophagy is a molecular process essential for the maintenance of cellular homeostasis, which appears to (i) decline with age and (ii) respond to physical exercise. In addition, recent evidence suggests a crosstalk between autophagy and toll-like receptor (TLR)-associated inflammatory responses. This study assessed the effects of aerobic exercise training on autophagy and TLR signaling in older subjects. Twentynine healthy women and men (age, 69.7 ± 1.0 year) were randomized to a training (TG) or a control (CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
5
41
1
1
Order By: Relevance
“…Exercise-induced Pink1 activation of Drp1 (112) could also target dysfunctional mitochondria for mitophagy. This idea is supported by recent data from Mejias-Pena et al (92) who found an increase in the protein abundance of autophagy proteins Beclin-1, Atg12, Atg16, and the LC3II/I ratio in blood mononuclear cells of elderly subjects after 8 weeks of aerobic exercise. Furthermore, 8 weeks of aerobic exercise has been reported to increase autophagy proteins Beclin-1, ATG7, and MuRF-1 in muscles of old mice (70).…”
Section: Foxo Proteins and The Ubiquitin Proteasome System (Ups) In Msupporting
confidence: 69%
“…Exercise-induced Pink1 activation of Drp1 (112) could also target dysfunctional mitochondria for mitophagy. This idea is supported by recent data from Mejias-Pena et al (92) who found an increase in the protein abundance of autophagy proteins Beclin-1, Atg12, Atg16, and the LC3II/I ratio in blood mononuclear cells of elderly subjects after 8 weeks of aerobic exercise. Furthermore, 8 weeks of aerobic exercise has been reported to increase autophagy proteins Beclin-1, ATG7, and MuRF-1 in muscles of old mice (70).…”
Section: Foxo Proteins and The Ubiquitin Proteasome System (Ups) In Msupporting
confidence: 69%
“…; Mejías‐Peña et al . ; Kim & Hood, ). He and colleagues () observed a decreased association of Beclin 1 with Bcl‐2 within 30 min of acute exercise, despite a rise in total protein levels of Beclin 1.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an increase in Beclin 1 protein expression in young muscle exposed to CCA. Previous reports have identified an increase in Beclin 1 following both acute and chronic exercise (He et al 2012;Ju et al 2016), but some opposing results have also been documented (McMillan et al 2015;Mejías-Peña et al 2016;Kim & Hood, 2017). He and colleagues (2012) observed a decreased association of Beclin 1 with Bcl-2 within 30 min of acute exercise, despite a rise in total protein levels of Beclin 1.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, autophagy negatively regulates inflammation by inducing changes on the TLR-mediated inflammatory response, as we recently showed [9]. On the other hand, autophagy may function as a negative counter-regulatory mechanism for inflammasome activation, thus providing a checkpoint to limit the development of inflammation [36].…”
Section: Discussionmentioning
confidence: 99%